Alveolar Measurements in Dental Anthropology: An Alternative Metric Technique in Cases of Postmortem Missing Teeth - Carmen Tanga; Joan Viciano (Forensic Sciences)
Background/Objectives: The aim of this study was to examine the relationship between the mesiodistal and buccolingual alveolar diameters and the usual crown and cervical diameters and to test the reliability of these alveolar measurements for their application in dental anthropology in cases of missing teeth. Methods: A total of 127 skeletal individuals from the identified osteological collection of Certosa Cemetery (Bologna, Italy) were used in this study. After the evaluation of limiting factors, only the central incisor to the second premolar was analysed due to a null or small sample size for the molars. The mesiodistal and buccolingual diameters were measured at the level of the crown, cervix and alveolus. The relationship between the mesiodistal and buccolingual crown or cervical diameters and the alveolar measurements was assessed. Results: The buccolingual alveolar diameters showed consistently significant relationships with their equivalent cervical and crown diameters, while the mesiodistal alveolar diameters did not show consistent relationships. Furthermore, the patterns of phenotypic variation were similar for the alveolar, cervical and crown areas. Thus, the alveolar areas appear to show similar levels of variability compared with the equivalent crown and cervical areas. Conclusions: Alveolar measurements may serve as suitable proxies in comparative phenotypic variation studies and can be considered a useful supplement to the standard odontometric data collection strategy. The measurements proposed in this study for the evaluation of the alveoli are a valid alternative in situations in which teeth are not available for measurement, such as in forensic and archaeological contexts.